Computerised control of DC motor field weakening and constant power performance - Fang, Lin Luo (2008)
This research report mainly concentrates to the Phase 2: field weakening operation. I have investigated various control methods to implement field weakening methodology. The control methods are: DSP-based control; neural network; nonlinear load-adaptive MIMO control; nonlinear MIMO speed sensorless control; nonlinear MIMO adaptive control.